Le fort de Verdun localisé - Dubeau, Pierre (Les Argoulets, 2024)
Keywords: Forts; Verdun

La cavalerie de Montréal. L'histoire du Royal Canadian Hussars (Montreal) - Kellett, Anthony; Linton, Steven; Cochrane, John (L'institut de cavalerie de Montréal, 2024)
Keywords: Combat; Milice

La vie de John Elsdale Molson - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont

DOHERTY, CHARLES JOSEPH - Glassford, Larry A. (Dictionnaire biographique du Canada, 2023)

CULLEN, MAURICE GALBRAITH - Prioul, Didier (Dictionnaire biographique du Canada, 2022)

BRAINERD, THOMAS CHALMERS - Cloutier, J.-Roger (Dictionnaire biographique du Canada, 2021)

“The Severity of This Service…” Canadien Inland Mariners in the Early Post-Conquest Era, 1760 to 1817 - More, John David (Université Queen's, 2021)
Keywords: Guerre; Navigation

La mutation vers un espace urbain moderne. Le projet de démantèlement des fortifications de Montréal - Beauchamp-Monfette, Joel (Cap-aux-Diamants, 2020)
issued: 2020-24-00
Keywords: Fortifications

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Continentals and Coureurs De Bois: The American Invasions of Canada and Illinois in the Revolutionary War - Keck, John D. (Sam Houston State University, 2018)
Keywords: Américains; Gouverneurs

Daily Life in Montreal during the Eighteenth Century - Turcot, Laurent (Montreal: The History of A North American City, 2018)
Keywords: Auberges; Cabarets; Danse; Hôtellerie; Marchés; Rues; Théâtre; Vêtements

Careful Coexistence: The Canadians and British in Montreal prior to 1800 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Américains; Britanniques; Gazette Littéraire de Montréal; Gouverneurs; Loyalistes; Marchands; Mesplet; Fleury; Protestants; Écossais

Montréal 1760: reddition de la Nouvelle-France - Lessard, Rénald (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Britanniques; Capitulation; Français

Montréal sous l’emprise des révolutionnaires américains - Monette, Pierre; Delisle, André (Cap-aux-Diamants, 2017)
issued: 2017-22-00
Keywords: Américains

Une ville fortifiée - Bélanger, Christian (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts

150 ans d’histoire militaire au centre-ville de Montréal - Joly, Diane (Revue militaire canadienne, 2016)
issued: 2016-24-00
Keywords: Dominion (square); Guerre; Monuments; Places publiques; Squares

Au temps où l'île Sainte-Hélène était militaire - Royer, Martin (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts; Île Sainte-Hélène

FYEN, ALFRED - Auger, Jean-François (Dictionnaire biographique du Canada, 2015)

With Thought and Faith: Henri Bourassa and the Great War - Keelan, Geoff (Worth Fighting For: Canada’s Tradition of War Resistance from 1812 to the War on Terror, 2015)
Keywords: Bourassa; Henri; Devoir (Le); Guerre

100 tonnes d'explosifs stockés sur l'avenue Dunlop! Intolérable! - Lester, Normand (Mémoire vivante, 2015)
issued: 2015-24-00/2016-24-00
Keywords: Armes; Forts; Rébellions

Louis-Joseph Papineau. Les débuts, 1808-1815 - Ostiguy, Raymond; Aubin, Georges (Éditions Histoire Québec, 2015)
Keywords: Avocats; Députés; Guerre; Milice; Papineau; Louis-Joseph

''It was impossible to make any further resistance'': The Final Act Plays Out before Montreal - Cubbison, Douglas R. (All Canada in the hands of the British: General Jeffery Amherst and the 1760 campaign to conquer New France, 2014)
Keywords: Capitulation

La gouvernance municipale avant la municipalité : Montréal, 1760-1840 - Fyson, Donald (La gouvernance montréalaise : de la ville-frontière à la métropole, 2014)

"Fidèle à Dieu, à la France, et au roi" : les retraites militaires de La Chapelle et de Beaujeu vers la Louisiane après la perte du Canada 1760-1762 - Gagné, Joseph (Université Laval, 2014)
Keywords: Capitulation

Charles-Madeleine Youville-Dufrost, prêtre et sa mère, Marguerite d'Youville - Mathieu, Jacques (Vivre la Conquête à travers plus de 25 parcours individuels, 2013)
Keywords: Dufrost de Lajemmerais; Marie-Marguerite (Youville; Marguerite d')

Lacorne Saint-Luc: l'odyssée d'un noble, 1711-1784 - Saint-Pierre, Marjolaine (Septentrion, 2013)
Keywords: Fourrure; Guerre; La Corne; Luc de (La Corne Saint-Luc ou Saint-Luc de La Corne); Marchands; Noblesse

An Examination of the Coverage of the War of 1812 in the Montreal Gazette, 1812-1815 - Perrone, Julie (Canadian Issues, 2012)
issued: 2012-23-00
Keywords: Guerre; Montreal Gazette

Moeurs, sociabilités et mentalités montréalaises: la vie quotidienne dans la ville au XVIIIe siècle - Turcot, Laurent (Histoire de Montréal et de sa région, 2012)
Keywords: Auberges; Cabarets; Danse; Hôtellerie; Marchés; Rues; Théâtre; Vêtements

Cohabiter avec et contre l'autre: Canadiens et Britanniques à Montréal avant 1800 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Américains; Britanniques; Gazette Littéraire de Montréal; Gouverneurs; Loyalistes; Marchands; Mesplet; Fleury; Protestants; Écossais

La guerre de 1812: Journal de Jacques Viger - Viger, Jacques; Andrès, Bernard (Les Presses de l'Université Laval, 2012)
Keywords: Maires; Viger; Jacques

The British Garrison and Montreal Society, 1830-1850 - Vineberg, Robert (Canadian Military History, 2012)
issued: 2012-24-00
Keywords: Armée; Britanniques; Garnison

The Colonial Landscapes of the Early Town - Coates, Colin M. (Metropolitan Natures: Environmental Histories of Montreal, 2011)

Le radicalisme tory à travers le prisme du Montreal Herald et la mobilisation des milices dans le district de Montréal (1834-1837) - Deschamps, François (Université du Québec à Montréal, 2011)
Keywords: Milice; Rébellions

The Surrender of Montreal to General Amherst de Francis Hayman et l'identité impériale britannique - Turcot, Laurent (Mens, 2011)
issued: 2011-23-00
Keywords: Capitulation; Guerre; Peinture

Jacques Viger et Joseph Mermet: naissance d’un écrivain (1814-1828) - Andrès, Bernard (Les Cahiers des dix, 2010)
Number: 64
Keywords: Maires; Viger; Jacques; Écrivains

"Monseigneur, pardonnez-moi parce que j'ai péché": la régulation de la dissidence au sein du clergé canadien, au moment de l'invasion américaine de 1775-1776 - Turgeon, Charles (Université de Montréal, 2010)
Keywords: Américains; Chartier de Lotbinière; Eustache; Floquet; Pierre-René; Huet de La Valinière; Pierre

Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (VLB Éditeur, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger; Jacques

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey; Daniel; Émeutes

Le fort et les poudrières du complexe militaire de l'île Sainte-Hélène - Royer, Martin (Université Laval, 2009)
Keywords: Armes; Fortifications; Forts; Île Sainte-Hélène

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet; Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard; Valentin; Journalistes; Librairie; Mesplet; Fleury

Le Roi, l'Église et la guerre: la prédication à Montréal au moment de la conquête (1750-1766) - Décary, Simon (Université de Montréal, 2008)
Keywords: Communautés religieuses; Sulpiciens

Les Pointeliers en guerre - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Armée; Guerre; Milice; Pointe-aux-Trembles; Quartiers

La stratégie lors de l'affrontement anglo-américain au Canada (1775-1776). Objets politiques et objectifs militaires - Nadeau, Charles André (Université Laval, 2008)
Keywords: Américains; Armée; Britanniques

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières; Pierre

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (University of British Columbia Press, 2006)
Keywords: Guerre; Quartiers; Verdun

A Man's a Man because of That: The Scots in the Canadian Military Experience - Klepak, H. P. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Armée; Écossais

WILSON, ERASTUS WILLIAM - Gagnon, Jean-Pierre (Dictionnaire biographique du Canada, 2005)

RODDICK, sir THOMAS GEORGE - Hanaway, Joseph (Dictionnaire biographique du Canada, 2005)

La milice du district de Montréal, 1787-1829: essai d'histoire socio-militaire - Lépine, Luc (Université du Québec à Montréal, 2005)
Keywords: Milice

MEREDITH, sir HENRY VINCENT - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Number: 75
Keywords: Guerre; Lachine; Émeutes

VALLÉE, CHARLES-AMÉDÉE - Tremblay, Marie J. (Dictionnaire biographique du Canada, 2005)

James McGill of Montreal : citizen of the Atlantic world - Cooper, John Irwin (Borealis Press, 2003)
Keywords: Autochtones; Fourrure; Marchands; McGill; James

The Last French and Indian War: an Inquiry Into a Safe-Conduct Issued in 1760 that Acquired the Value of a Treaty in 1990 - Vaugeois, Denis (McGill-Queen's University Press et Septentrion, 2002)
Translators: _:n41953
Keywords: Autochtones; Français

L'organisation de la milice de la région montréalaise de 1792 à 1837: de la paroisse au comté - Dion, Dominique; Legault, Roch (Bulletin d'histoire politique, 2000)
issued: 2000-24-00/2000-21-00
Keywords: Milice

GREENSHIELDS, EDWARD BLACK - Burr, Gordon (Dictionnaire biographique du Canada, 1998)

LACHAPELLE, EMMANUEL-PERSILLIER - Desrosiers, George; Gaumer, Benoît; Keel, Othmar (Dictionnaire biographique du Canada, 1998)

GIRDWOOD, GILBERT PROUT - Goulet, Denis (Dictionnaire biographique du Canada, 1998)

BURLAND, JEFFREY HALE - Keating, Peter (Dictionnaire biographique du Canada, 1998)

HÉBERT, LOUIS-PHILIPPE - Lacasse, Yves (Dictionnaire biographique du Canada, 1998)

BOUCHER DE BOUCHERVILLE, sir CHARLES - Munro, Kenneth (Dictionnaire biographique du Canada, 1998)

OUIMET, JOSEPH-ALDRIC - Munro, Kenneth (Dictionnaire biographique du Canada, 1998)

Les habits rouges et les Patriotes - Senior, Elinor Kyte (VLB, 1997)
Keywords: Britanniques; Rébellions

La consommation de viande à Montréal au XVIIe et au XVIIIe siècles - Cossette, Évelyne (Archéologies québécoises, 1995)
Keywords: Alimentation; Auberges; Champ-de-Mars; Fortifications; Hôpital Général; Hôpitaux; Place Royale; Places publiques; Wurtele; Jacob

La fin des alliances franco-indiennes: enquête sur un sauf-conduit de 1760 devenu un traité en 1990 - Vaugeois, Denis (Boréal, 1995)
Keywords: Autochtones; Français

OGILVIE, ALEXANDER WALKER - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1994)

CAMPBELL, FRANCIS WAYLAND - Milner, Elizabeth Hearn (Dictionnaire biographique du Canada, 1994)

LAVIGNE, ERNEST - Poirier, Lucien (Dictionnaire biographique du Canada, 1994)

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger; Jacques

Montréal: Entrepôt and Military Logistics Centre - Charbonneau, André; Lafrance, Marc; Poirier, Monique (Opening the Gates of Eighteenth-Century Montréal, 1992)
Keywords: Armes; Armée

Montréal: entrepôt militaire et centre logistique - Charbonneau, André; Lafrance, Marc; Poirier, Monique (Montréal, ville fortifiée au XVIIIe siècle, 1992)
Keywords: Armes; Armée

BELLINGHAM, SYDNEY ROBERT - Daley, Robert C. (Dictionnaire biographique du Canada, 1990)

DESBARATS, GEORGE-ÉDOUARD - Galarneau, Claude (Dictionnaire biographique du Canada, 1990)

OGILVIE, WILLIAM WATSON - Levine, Allan (Dictionnaire biographique du Canada, 1990)

KINGSFORD, WILLIAM - Taylor, M. Brook (Dictionnaire biographique du Canada, 1990)

Provincial Troops in the Montreal Area 1775-1784 - Fryer, Mary Beacock (The Loyalists of Quebec 1774-1825: A Forgotten History, 1989)
Keywords: Loyalistes

MONDELET, JEAN-MARIE (Dictionnaire biographique du Canada, 1988)

DULONGPRÉ, LOUIS - Bazin, Jules (Dictionnaire biographique du Canada, 1988)

MILLAR, JAMES - Deslauriers, Peter (Dictionnaire biographique du Canada, 1988)

QUESNEL, JULES-MAURICE - Deslauriers, Peter (Dictionnaire biographique du Canada, 1988)

O’SULLIVAN, MICHAEL - Dever, Alan R. (Dictionnaire biographique du Canada, 1988)

MOLSON, JOHN - Dubuc, Alfred (Dictionnaire biographique du Canada, 1988)

BLACKWOOD, THOMAS - Frost, Stanley Brice (Dictionnaire biographique du Canada, 1988)

PÉPIN, JOSEPH - Gauthier, Raymonde (Dictionnaire biographique du Canada, 1988)

WALKER, WILLIAM - Miller, Carmen (Dictionnaire biographique du Canada, 1988)

PORTEOUS, ANDREW - Momryk, Myron (Dictionnaire biographique du Canada, 1988)

CUVILLIER, AUSTIN - Monet, Jacques; Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1988)

MASSON, JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1988)

RASTEL DE ROCHEBLAVE, PIERRE DE - Ouellet, Marc; Dufour, Pierre (Dictionnaire biographique du Canada, 1988)

POTHIER, TOUSSAINT - Pothier, Philippe (Dictionnaire biographique du Canada, 1988)

BADGLEY, FRANCIS (1767-1841) - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1988)

GUY, LOUIS - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1988)

ROY PORTELANCE, LOUIS - St-Georges, Lise (Dictionnaire biographique du Canada, 1988)

AULDJO, GEORGE - Tulchinsky, Gérald J. J. (Dictionnaire biographique du Canada, 1988)

FORSYTH, JOHN - Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1988)

THAIN, THOMAS - Allaire, Gratien (Dictionnaire biographique du Canada, 1987)

McKAY, WILLIAM - Allen, Robert S. (Dictionnaire biographique du Canada, 1987)

HENRY, ALEXANDER - Armour, David A. (Dictionnaire biographique du Canada, 1987)

BLEAKLEY, JOSIAH - Armour, David Arthur (Dictionnaire biographique du Canada, 1987)

CALDWELL, WILLIAM - Bensley, Edward Horton (Dictionnaire biographique du Canada, 1987)

ROUSSEAU, DOMINIQUE - Derome, Robert (Dictionnaire biographique du Canada, 1987)

FLEMING, JOHN - Deslauriers, Peter (Dictionnaire biographique du Canada, 1987)

DESRIVIÈRES, FRANÇOIS - Frost, Stanley Brice (Dictionnaire biographique du Canada, 1987)

RICHARDSON, JOHN - Greenwood, F. Murray (Dictionnaire biographique du Canada, 1987)

SEWELL, STEPHEN - Greenwood, F. Murray (Dictionnaire biographique du Canada, 1987)

CHARTIER DE LOTBINIÈRE, MICHEL-EUSTACHE-GASPARD-ALAIN - Hamelin, Marcel (Dictionnaire biographique du Canada, 1987)

LOEDEL, HENRY NICHOLAS CHRISTOPHER - Janson, Gilles (Dictionnaire biographique du Canada, 1987)

MECHTLER, GUILLAUME-JOSEPH - Kallmann, Helmut (Dictionnaire biographique du Canada, 1987)

BIGAULT D’AUBREVILLE, LOUIS-NICOLAS-EMMANUEL DE - Kyte Senior, Elionor (Dictionnaire biographique du Canada, 1987)

McCORD, THOMAS - Kyte Senior, Elionor (Dictionnaire biographique du Canada, 1987)

McMILLAN, ARCHIBALD - Lambert, James H.; Macmillan, David D. (Dictionnaire biographique du Canada, 1987)

CHAUSSEGROS DE LÉRY, LOUIS-RENÉ - Legault, Roch (Dictionnaire biographique du Canada, 1987)

LAMOTHE, JOSEPH-MAURICE - Leighton, J. Douglas (Dictionnaire biographique du Canada, 1987)

SELBY, GEORGE - Lessard, Renald (Dictionnaire biographique du Canada, 1987)

GRAY, JOHN - Miller, Carman (Dictionnaire biographique du Canada, 1987)

ERMATINGER, FREDERICK WILLIAM - Momryk, Myron (Dictionnaire biographique du Canada, 1987)

SUTHERLAND, DANIEL - Momryk, Myron (Dictionnaire biographique du Canada, 1987)

FROBISHER, BENJAMIN JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1987)

McGILLIVRAY, WILLIAM - Ouellet, Fernand (Dictionnaire biographique du Canada, 1987)

DeGAUGREBEN, FRIEDRICH - Raudzens, George Karl (Dictionnaire biographique du Canada, 1987)

DAVID, DAVID - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1987)

JOHNSON, sir JOHN - Thomas, Earle (Dictionnaire biographique du Canada, 1987)

GARDEN, GEORGE - Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1987)

WHITE, ANDREW - Witham, John (Dictionnaire biographique du Canada, 1987)

JOSEPH, HENRY - Wolff, Annette R. (Dictionnaire biographique du Canada, 1987)

DOUCET, NICOLAS-BENJAMIN - Boucher, Jacques (Dictionnaire biographique du Canada, 1985)

MORRIS, WILLIAM - Bridgman, Harry (Dictionnaire biographique du Canada, 1985)

McKAY, THOMAS - Bush, E.F. (Dictionnaire biographique du Canada, 1985)

GIROUARD, JEAN-JOSEPH - Chassé, Béatrice (Dictionnaire biographique du Canada, 1985)

HERTEL DE ROUVILLE, JEAN-BAPTISTE-RENÉ - Courville, Serge (Dictionnaire biographique du Canada, 1985)

LACROIX, JANVIER-DOMPTAIL - Courville, Serge (Dictionnaire biographique du Canada, 1985)

VIGER, LOUIS-MICHEL - De Lorimier, Michel (Dictionnaire biographique du Canada, 1985)

GERRARD, SAMUEL - Deslauriers, Peter (Dictionnaire biographique du Canada, 1985)

GAMELIN, PIERRE - Fortin, Lionel (Dictionnaire biographique du Canada, 1985)

ROY, JOSEPH - Galarneau, France (Dictionnaire biographique du Canada, 1985)

SCOTT, WILLIAM HENRY - Gouin, Jacques (Dictionnaire biographique du Canada, 1985)

JOBIN, ANDRÉ - Greenwood, F. Murray (Dictionnaire biographique du Canada, 1985)

PELTIER, TOUSSAINT - Lefebvre, Jean-Jacques (Dictionnaire biographique du Canada, 1985)

HART, BENJAMIN - Miller, Carman (Dictionnaire biographique du Canada, 1985)

BARBIER, LOUIS-MARIE-RAPHAËL - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1985)

VIGER, JACQUES - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1985)

FABRE, ÉDOUARD-RAYMOND - Roy, Jean-Louis (Dictionnaire biographique du Canada, 1985)

CLITHEROW, JOHN - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1985)

Red Coats and Patriotes: The Rebellions in Lower Canada 1837-38 - Senior, Elinor Kyte (Canada's Wings, 1985)
Keywords: Britanniques; Rébellions

MOLSON, JOHN - Tremblay, Robert; Dubuc, Alfred (Dictionnaire biographique du Canada, 1985)

VANFELSON, GEORGE - Vachon, Claude (Dictionnaire biographique du Canada, 1985)

WARBURTON, GEORGE DROUGHT - Waterston, Elizabeth (Dictionnaire biographique du Canada, 1985)

VAVASOUR, HENRY WILLIAM - Woodward, Frances M. (Dictionnaire biographique du Canada, 1985)

ROBERTSON, DANIEL - Armour, David Arthur (Dictionnaire biographique du Canada, 1983)

BLONDEAU, MAURICE-RÉGIS - Béland, François (Dictionnaire biographique du Canada, 1983)

TESTARD LOUVIGNY DE MONTIGNY, JEAN-BAPTISTE-PIERRE - Béland, François (Dictionnaire biographique du Canada, 1983)

DOBIE, RICHARD - Burgess, Joanne (Dictionnaire biographique du Canada, 1983)

FORETIER, PIERRE - Burgess, Joanne (Dictionnaire biographique du Canada, 1983)

OGILVY, JOHN - Campbell, Marjorie Wilikins (Dictionnaire biographique du Canada, 1983)

LE COMTE DUPRÉ, JEAN-BAPTISTE - Cyr, Céline (Dictionnaire biographique du Canada, 1983)

CRUICKSHANK, ROBERT - Derome, Robert (Dictionnaire biographique du Canada, 1983)

HAZEN, MOSES - Everest, Allan S. (Dictionnaire biographique du Canada, 1983)

EDWARDS, EDWARD - Hare, John E. (Dictionnaire biographique du Canada, 1983)

QUESNEL, JOSEPH - Hare, John E. (Dictionnaire biographique du Canada, 1983)

BLAKE, CHARLES - Janson, Gilles (Dictionnaire biographique du Canada, 1983)

GUY, PIERRE - Joanette, Ginette; John, Claire (Dictionnaire biographique du Canada, 1983)

CALDWELL, JAMES - Labrèque, Marie-Paule R. (Dictionnaire biographique du Canada, 1983)

CHARLAND, LOUIS - Langelier, Gilles (Dictionnaire biographique du Canada, 1983)

GUY, ÉTIENNE - Langelier, Gilles (Dictionnaire biographique du Canada, 1983)

DE LISLE, JEAN-GUILLAUME - Lortie, Léon (Dictionnaire biographique du Canada, 1983)

DUNLOP, JAMES - Macmillan, David S.; Richardson, A.J.H. (Dictionnaire biographique du Canada, 1983)

GRAY, EDWARD WILLIAM - Momryk, Myron (Dictionnaire biographique du Canada, 1983)

TODD, ISAAC - Momryk, Myron (Dictionnaire biographique du Canada, 1983)

FROBISHER, JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

McBEATH, GEORGE - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

McTAVISH, SIMON - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

GUERNON, Belleville, FRANÇOIS - Porter, John R. (Dictionnaire biographique du Canada, 1983)

LIÉNARD DE BEAUJEU DE VILLEMONDE, LOUIS - Ruddy, David Daniel (Dictionnaire biographique du Canada, 1983)

CLARKE, HENRY JOSEPH - Clark, Lovell C. (Dictionnaire biographique du Canada, 1982)

MacDOUGALL, DUGALD LORN - Doyon, Charles (Dictionnaire biographique du Canada, 1982)

MORRIS, ALEXANDER - Friesen, Jean (Dictionnaire biographique du Canada, 1982)

HIBBARD, ASHLEY - Gervais, Gaétan (Dictionnaire biographique du Canada, 1982)

GERVAIS, GUALBERT - Hardy, René (Dictionnaire biographique du Canada, 1982)

BUCHANAN, ISAAC - McCalla, Douglas (Dictionnaire biographique du Canada, 1982)

HART, THEODORE - Miller, Carman (Dictionnaire biographique du Canada, 1982)

McKIERNAN, CHARLES, Joe Beef - Provencher, Jean (Dictionnaire biographique du Canada, 1982)

DAVID, ELEAZAR DAVID - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1982)

MICHEL, sir JOHN - Stacey, C. P. (Dictionnaire biographique du Canada, 1982)

SMITH, WILLIAM OSBORNE - Stacey, C. P. (Dictionnaire biographique du Canada, 1982)

COURSOL, CHARLES-JOSEPH - Ste.Croix, Lorne (Dictionnaire biographique du Canada, 1982)

JOSEPH, ABRAHAM - Wolff, Annette R. (Dictionnaire biographique du Canada, 1982)

The British Army and Sport in Canada: Case Studies of the Garrison of Halifax, Montreal and Kingston to 1871 - Day, Robert Douglas (Université d'Alberta, 1981)
Keywords: Armée; Britanniques; Garnison

British Regulars in Montreal: An Imperial Garrison, 1832-1854 - Senior, Elinor Kyte (McGill-Queen's University Press, 1981)
Keywords: Armée; Britanniques; Garnison

Roots of the Canadian Army; Montreal District, 1846-1870 - Senior, Elinor Kyte (The Society of the Montreal Military and Maritime Museum / La Société du musée militaire et maritime de Montréal, 1981)
Keywords: Armée; Milice

TESTARD DE MONTIGNY, JEAN-BAPTISTE-PHILIPPE - Armour, David Arthur (Dictionnaire biographique du Canada, 1980)

LE VERRIER DE ROUSSON, LOUIS - Chaput, Donald (Dictionnaire biographique du Canada, 1980)

PAYEN DE NOYAN ET DE CHAVOY, PIERRE-JACQUES - Chaput, Donald (Dictionnaire biographique du Canada, 1980)

GAMELIN, PIERRE-JOSEPH - Dumais, Raymond (Dictionnaire biographique du Canada, 1980)

RIGAUD DE VAUDREUIL DE CAVAGNIAL, PIERRE DE, marquis de Vaudreuil - Eccles, William John (Dictionnaire biographique du Canada, 1980)

FELTZ, CHARLES-ELEMY-JOSEPH-ALEXANDRE-FERDINAND - Janson, Gilles (Dictionnaire biographique du Canada, 1980)

VARIN DE LA MARRE, JEAN-VICTOR - Lachance, André (Dictionnaire biographique du Canada, 1980)

AILLEBOUST DE LA MADELEINE, FRANÇOIS-JEAN-DANIEL D’ - Paré, Hélène (Dictionnaire biographique du Canada, 1980)

CIRIER, ANTOINE - Porter, John R. (Dictionnaire biographique du Canada, 1980)

FLEURY DESCHAMBAULT, JOSEPH - Rodger, Andrew (Dictionnaire biographique du Canada, 1980)

TROTTIER DUFY DESAUNIERS, THOMAS-IGNACE - Roy, Jacqueline (Dictionnaire biographique du Canada, 1980)

RIGAUD DE VAUDREUIL, FRANÇOIS-PIERRE DE - Roy, Jacqueline; Hamelin, Jean (Dictionnaire biographique du Canada, 1980)

LEGARDEUR DE REPENTIGNY, LOUIS - Taillemite, Étienne (Dictionnaire biographique du Canada, 1980)

NICKINSON, JOHN - Edwards, Murray D. (Dictionnaire biographique du Canada, 1977)

MONDELET, DOMINIQUE - Gibbs, Elizabeth (Dictionnaire biographique du Canada, 1977)

NAPIER, DUNCAN CAMPBELL - Leighton, Douglas (Dictionnaire biographique du Canada, 1977)

MORIN, AUGUSTIN-NORBERT - Paradis, Jean-Marc (Dictionnaire biographique du Canada, 1977)

ERMATINGER, FREDERICK WILLIAM - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1977)

FORBES, CHARLES JOHN - Thompson, John Beswarick (Dictionnaire biographique du Canada, 1977)

The Provincial Cavalry in Lower Canada 1837-50 - Senior, Elinor Kyte (Canadian Historical Review, 1976)
Number: 1
Keywords: Milice

An Imperial Garrison in its Colonial Setting. British Regulars in Montreal, 1832-1854 - Senior, Elinor Kyte (Université McGill, 1976)
Keywords: Armée; Britanniques; Garnison

COUAGNE, RENÉ - Igartua, José (Dictionnaire biographique du Canada, 1974)

LE MOYNE DE LONGUEUIL, CHARLES, baron de LONGUEUIL - Lachance, André (Dictionnaire biographique du Canada, 1974)

MAURIN, FRANÇOIS - Lachance, André (Dictionnaire biographique du Canada, 1974)

BURTON, RALPH - Neatby, Hilda (Dictionnaire biographique du Canada, 1974)

LE COMTE DUPRÉ, JEAN-BAPTISTE - Quesnel, Yves (Dictionnaire biographique du Canada, 1974)

ADHÉMAR DE LANTAGNAC, GASPARD - Russ, C. J. (Dictionnaire biographique du Canada, 1974)

The British Garrison in Montreal in the 1840's - Senior, Elinor Kyte (Journal of the Society for Army Historical Research, 1974)
Number: 210
Keywords: Armée; Britanniques; Garnison

COFFIN, WILLIAM FOSTER - Morton, Desmond (Dictionnaire biographique du Canada, 1972)

MONDELET, CHARLES - Nish, Elizabeth (Dictionnaire biographique du Canada, 1972)

L'invasion du Canada en 1775, d'après les historiens canadiens-français - Kelly, John E. (Université Laval, 1941)
Keywords: Américains; Armée; Historiens

The Fenian Invasion of Canada of 1866 and 1870 and the Operations of the Montreal Militia Brigade in Connection Therewith - Campbell, F. W. (s.é., 1904)
Keywords: Féniens; Milice

Montreal and Its Fortifications - Sandham, Alfred (Daniel Rose, 1874)
Keywords: Fortifications